Interview with Professor Chaitanya Mishra - Subedi, Madhusudan; Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2021)
Professor Chaitanya Mishra teaches Sociology to MPhil/PhD students at Tribhuvan University (TU), Nepal. His research focuses on macrosociology, politics, social change, and social stratification. He is an author/co-author, and co-editor of 10 books and about 250 articles. He believes that all sciences should contribute to public education, and frequently contributes to public debates through the media. He started his career in 1978 as a researcher at the Institute of Nepal and Asian Studies, TU. In 1981, he was appointed the founder Chair of the Central Department of Sociology/Anthropology, TU. He has written on the development of sociological knowledge in Nepal, its disciplinary growth, empirical and theoretical orientations, as well as strategies that could be adopted to meet contemporary disciplinary challenges. His contributions have led to theoretical debates on the issues of development or underdevelopment of Nepali society as well as the nature and causes of economic and political divisions and alternative trajectory of change. Professor Mishra served as a member of Nepal’s National Planning Commission (1994-95), founding president of Nepal Sociological Association (2017-18), Fulbright Visiting Professor and Hubert Humphrey Professor of Sociology at Macalester College (2015-16), and founding Executive Chair of the Policy Research Institute (2018-19) of the Government of Nepal.